Spiritual Business Communication Model: Integration of Trust and Brotherhood in Sharia Cooperatives - Herdiana Herdiana; Imron Rosyadi (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Contemporary business world that is solely profit-oriented has eroded the values of trust and brotherhood which are the foundation of sustainable business relationships. This research aims to formulate a spiritual business communication model that integrates the value of trust from modern business communication theory with the value of ukhuwah islamiyah as an instrument of dakwah bil hal in the context of Islamic cooperatives. This research uses a qualitative approach with library research type, analyzing various literatures in the fields of business communication, Islamic ethics, and Islamic economics through qualitative content analysis and critical analysis techniques. The results show that the spiritual business communication model consists of five main components: (1) spiritual foundation in the form of sincere intention; (2) operational principles consisting of a triad of Islamic values (amanah, shiddiq, and ukhuwah); (3) multi-level communication strategies (vertical, horizontal, and external); (4) hybrid media and communication channels; and (5) outcomes in the form of triple benefits (spiritual, social, and economic). This model is circular and dynamic with a positive feedback loop mechanism that makes it sustainable. The integration of trust and ukhuwah produces the concept of "spiritual trust" which is more profound because it is based not only on rational calculations but also on spiritual beliefs. The implementation of this model makes all Islamic cooperative activities an effective practice of dakwah bil hal, creating confidence for managers and comfort for members. This research contributes theoretically by enriching the literature on business communication based on Islamic spirituality and practically can serve as a guide for Islamic cooperative managers in designing communication strategies that are not only effective in business but also spiritually meaningful.